2019
DOI: 10.1002/nau.24098
|View full text |Cite
|
Sign up to set email alerts
|

Urethro‐vaginal reflux during micturition: An underestimated cause of urinary incontinence in adult women

Abstract: Aims: To evaluate if urethrovaginal reflux (UVR) is an underestimated cause of insensible or postmicturition incontinence in adult women. Methods: An observational and retrospective study was carried out on the computerized records of a neuro-urology department. Female patients who had insensible or postmicturition incontinence were investigated. Retrograde and voiding urethrocystography (UCG), urodynamic evaluation, urethral pressure profilometry, and anamnestic and clinical examination had to be available. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Motavasseli et al . reported that vaginal reflux during micturition is an underidentified cause of urinary incontinence in adult women and vaginal finger insertion can be used to manage it as well 3 . In our experience, many women have feelings of resistance toward vaginal finger insertion.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Motavasseli et al . reported that vaginal reflux during micturition is an underidentified cause of urinary incontinence in adult women and vaginal finger insertion can be used to manage it as well 3 . In our experience, many women have feelings of resistance toward vaginal finger insertion.…”
Section: Discussionmentioning
confidence: 73%
“…Motavasseli et al reported that vaginal reflux during micturition is an underidentified cause of urinary incontinence in adult women and vaginal finger insertion can be used to manage it as well. 3 In our experience, many women have feelings of resistance toward vaginal finger insertion. Thus, to evacuate entrapped fluid, it may be a much more acceptable method to put a towel between the legs and apply abdominal pressure or cross the legs after bathing.…”
Section: Discussionmentioning
confidence: 94%
“…Obstructive vaginal lesions and urogenital malformations are frequently associated with this condition. Obstructive lesions appear early in life, but VVR typically occurs in prepubertal girls with a prevalence rate of 12-15% and is anticipated to become nearly absent in middle age, which is rationally described by gradual bladder descent and anatomical modification of the vesicourethral angle [ 3 , 6 , 7 ]. There are few reports of VVR causing urocolpos in adult women, such as Motavasseli et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly seen in children and is caused by an anatomical abnormality such as the vaginal septum, hypoplastic vagina, or imperforate hymen [ 2 ]. VVR typically occurs in young children and prebuttal females with a prevalence rate of 12-15% and is anticipated to become nearly absent in middle age [ 3 ]. This condition has a variable clinical presentation, including abdominal pain, abdominal distension, urinary incontinence, recurrent urinary tract infections (UTIs), nocturnal enuresis, vaginitis, and vaginal discharge [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation